2021
DOI: 10.1155/2021/5589487
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Path Loss Channel Characterization Based on Air‐to‐Air Ground Reflection Channel Modeling for UAV‐Enabled Wireless Communications

Abstract: The purpose of this work was to investigate the air-to-air channel model (A2A-CM) for unmanned aerial vehicle- (UAV-) enabled wireless communications. Specifically, a low-altitude small UAV needs to characterize the propagation mechanisms from ground reflection. In this paper, the empirical path loss channel characterizations of A2A ground reflection CM based on different scenarios were presented by comparing the wireless communication modules for UAVs. Two types of wireless communication modules both WiFi 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In this work, authors suggested to use a three-dimensional (3D) non-stationary geometry-based stochastic model for air-to-air channels in UAV communication. In current literature, Broadly used low-power radios that are designed based on IEEE 802.15.4 [377], IEEE 802.11 [378] [379] and LoRa standards [380] have been used to experimentally characterize the air-to-air propagation channel [381]. However, the influence of the Doppler spectrum and antenna orientation of air-to-air channels have been poorly addressed in the literature and required further investigation [138].…”
Section: B Channel Modelingmentioning
confidence: 99%
“…In this work, authors suggested to use a three-dimensional (3D) non-stationary geometry-based stochastic model for air-to-air channels in UAV communication. In current literature, Broadly used low-power radios that are designed based on IEEE 802.15.4 [377], IEEE 802.11 [378] [379] and LoRa standards [380] have been used to experimentally characterize the air-to-air propagation channel [381]. However, the influence of the Doppler spectrum and antenna orientation of air-to-air channels have been poorly addressed in the literature and required further investigation [138].…”
Section: B Channel Modelingmentioning
confidence: 99%